The Implications of Karaeng Pattingalloang's Character Values on the Formation of National Character: Implikasi Nilai-Nilai Karakter Karaeng Pattingalloang Terhadap Pembentukan Karakter Bangsa - Rahmawati Rahmawati; Naya Naya; Ilham Samudra Sanur (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2026)
Character education has a crucial role in producing a generation with strong personalities, high moral standards, and exceptional academic performance. Social dynamics are common in Indonesia, which emphasises how vital it is to improve character education through contextual learning. This study looks into Karaeng Pattingalloang's moral principles and how they relate to the growth of character education in Indonesia. By gathering numerous pertinent literature sources from books, character education journals, and online articles that can be analysed with an emphasis on searching for multiple keywords and flexible publication years, this study was carried out using a descriptive qualitative approach with a literature review method. According to the study's findings, Karaeng Pattingalloang displays important character traits like intellectualism and a love of learning, cultural tolerance and openness, visionary leadership and diplomatic abilities, integrity, and nationalism. These ideals are highly relevant in today's education, particularly when it comes to using history classes to help students internalise the admirable qualities of national heroes. It is anticipated that incorporating Karaeng Pattingalloang's character qualities into education will mould students into critical thinkers, open-minded individuals, honest people, and patriots. This result highlights how Karaeng Pattingalloang's exemplary character might work as a crucial historical basis for bolstering character education in Indonesia in the face of globalization's problems.